2022
DOI: 10.21873/anticanres.15697
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Afatinib Outcomes in Advanced Non–small Cell Lung Cancer Harboring EGFR Mutations

Abstract: Background/Aim: Afatinib is a standard treatment for patients with advanced non-small cell lung cancer (NSCLC) harboring epidermal growth factor receptor (EGFR) mutations. Osimertinib can overcome the treatment resistance-associated EGFR T790M mutation, and the sequence of afatinib followed by osimertinib is an effective therapeutic strategy for NSCLC patients. This study comprehensively evaluated the outcomes of sequential therapy following frontline afatinib and identified predictive factors for T790M mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…Previous studies have shown that secondary T790M mutation is an important biomarker for subsequent osimertinib therapy in advanced EGFR-mutated NSCLC patients who have progressive disease after first-line 1G/2G EGFR-TKI treatment because osimertinib prominently benefits the ORR and PFS of patients with secondary T790M mutation. 17 , 26 , 27 In previous studies, including prospective studies (e.g. the AURA Extension and AURA2 trials) and real-world clinical studies, the acquired T790M detection rates ranged from 50% to 60%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that secondary T790M mutation is an important biomarker for subsequent osimertinib therapy in advanced EGFR-mutated NSCLC patients who have progressive disease after first-line 1G/2G EGFR-TKI treatment because osimertinib prominently benefits the ORR and PFS of patients with secondary T790M mutation. 17 , 26 , 27 In previous studies, including prospective studies (e.g. the AURA Extension and AURA2 trials) and real-world clinical studies, the acquired T790M detection rates ranged from 50% to 60%.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, 36.8% of the 36 patients with negative T790M upon the first biopsy showed positive T790M mutation in the second re-biopsy [ 28 ], indicating the benefit of repeated biopsy. In addition, comprehensive genetic testing with a combination of tissue and liquid biopsies can enrich the positive rate for detecting the T790M mutation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…All 172 study patients were obtained from the Chang Gung Research Database [ 17 , 18 , 19 , 20 ], which is an integrated database with multi-institutional standardized electronic medical records from all branches of Chang Gung Memorial Hospital (CGMH) in Taiwan, including information from the cancer registry. This study included the clinical data of patients from the cancer registry in the Linkou, Kaohsiung, Keelung, and Chiayi branches of CGMH from 2010 to 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Acquired resistance to EGFR-TKI therapies typically develops while the patient is receiving an EGFR-TKI and after a documented response or evidence of disease control [ 25 ]. Among resistance-inducing genes, the EGFR T790M is a rare mutation known to have an important clinical impact and has been identified as the most common mechanism for acquired resistance to EGFR-TKIs, observed in nearly two-thirds of cases that progress following successful EGFR-TKI therapy [ 26 , 27 ]. The poor therapeutic response to EGFR-TKIs is associated with the high allelic frequency of the T790M EGFR mutation [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%